2019
DOI: 10.1108/ijchm-09-2017-0565
|View full text |Cite
|
Sign up to set email alerts
|

Are tattoos still a taboo?

Abstract: Purpose As tattoos increase in popularity, questions persist regarding their impact on customer perceptions. To help shed light into this issue, this paper aims to explore the impact of tattooed restaurant servers in the context of service failures. Through the agency and communion theory, the authors propose that a female server with tattoos induces higher levels of negative word of mouth (WOM) intention than her male counterpart. Furthermore, the authors propose that perceived competence mediates this effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…However, more recently, authors such as Kosut (2006Kosut ( , 2014 challenge the widely held opinion of tattoos belonging to sub-cultures, low and middle-classes or underground and deviant individuals by highlighting the relationship between tattoos and mainstream consumer culture, identifying their new status as a trendy consumer item. Tattoos have continued to increase in popularity (Ozanne et al, 2019;Tews & Stafford, 2019). In fact, in 2015, Statista reported that 30% of adults between 25-39 years old in the UK had a tattoo (Statista, 2015), whilst more recently they found that 40% of UK adults have at least one tattoo (Statista, 2018).…”
Section: Visible Body Modificationsmentioning
confidence: 99%
“…However, more recently, authors such as Kosut (2006Kosut ( , 2014 challenge the widely held opinion of tattoos belonging to sub-cultures, low and middle-classes or underground and deviant individuals by highlighting the relationship between tattoos and mainstream consumer culture, identifying their new status as a trendy consumer item. Tattoos have continued to increase in popularity (Ozanne et al, 2019;Tews & Stafford, 2019). In fact, in 2015, Statista reported that 30% of adults between 25-39 years old in the UK had a tattoo (Statista, 2015), whilst more recently they found that 40% of UK adults have at least one tattoo (Statista, 2018).…”
Section: Visible Body Modificationsmentioning
confidence: 99%